UN human rights treaty bodies : law and legitimacy - Keller, Helen, 1964-; Ulfstein, Geir, 1951-; Grover, Leena (Cambridge, UK : Cambridge University Press, 2012)
'The effective implementation of human rights treaty obligations in national law is subject to increasing attention. The main responsibility for the international monitoring of national implementation at the global level is entrusted to the UN human rights treaty bodies. These bodies are established by the respective human rights conventions and are composed of independent experts. This book examines three aspects of these bodies: the legal aspects of their structure, functions and decisions; their effectiveness in ensuring respect for human rights obligations; and the legitimacy of these bodies and their decisions. Containing contributions from a variety of eminent legal experts, including present and former members of the treaty bodies, the analysis should be read in light of the ongoing effort to strengthen treaty bodies under the auspices of the UN High Commissioner for Human Rights and with the involvement of relevant stakeholders'--
Machine generated contents note: 1. Introduction / Helen Keller and Geir Ulfstein; 2. Examination of state reports / Walter Kalin; 3. Individual complaints / Geir Ulfstein; 4. General comments of the Human Rights Committee and their legitimacy / Helen Keller and Leena Grover; 5. The protection of economic and social rights: a particular challenge? / Urfan Khaliq and Robin Churchill; 6. Aspects of human rights interpretation by the UN Treaty bodies / Birgit Schltter; 7. UN Treaty bodies and the Human Rights Council / Nigel S. Rodley; 8. The legal status of decisions by human rights treaty bodies in national law / Rosanne van Alebeek and Andre Nollkaemper; 9. Conclusions / Helen Keller and Geir Ulfstein.
Includes bibliographical references (p. 426-445) and index.
Keywords: United Nations; Human rights; International agencies; Treaties